RANCANG BANGUN APLIKASI MOBILE REMOTE CONTROL BERBASIS ANDROID PADA ROBOT LEGO MINDSTRORM NXT 2.0 - Pura, Dona Pramana (Jurusan Informatika Universitas Tanjungpura, 2014)
Today the development of technology especiallyÂ Android smartphone is increase. Many various ofAndroid application that help human life are developed.In the same time of developing smartphone technology,robotic technology is also growing. Many miniaturerobotic technology (microbot) has ability to mimic theoriginal robot. One of the famous robotic technology isLEGO Mindstorm NXT with NXT-G platform.LegoMindstorm NXT 2.0 gives the user ability to constructÂ the robot by using a few motors and sensors (touchsensor, light sensor, ultrasonic sensor, temperaturesensor, and sound sensor). However, processingcapacity, memory, and communication ability ofLEGO NXT are far behind what is offered on asmartphone device. Lego Mindstorm NXT 2.0 onlyoffers the capacity of flash memory 256kb and 64kb ofRAM.Because of that reason, the writer create LegoNXT controller applications embedded in smartphonesbased on Android. The Intelligence of robot that usedto put in the brick move into this application. Thisgives us a great advantage because the current androidsmartphones has higher specifications than the brickcomponents (brain) of Lego NXT. For comparison,android smartphones owned 2GB of RAM and 2-64GB storage capacity. The brick of Lego NXT only has64kb RAM and 256kb of flash memory.Theapplications also allows the robot to switch the modesof manual control mode, control through accelerometer,making robot avoid the obstacle, and line followerrobot. After going through the black box testing, all ofthe functions in application is running according to itsÂ function. Based on the kompetibility testing, theapplication also running well on a variety of differentversions of Andoid devices.